Heavy metal detection kit. - Yusof, Nor Azah (2008)

(untitled)
The present invention relates to a kit for detecting the presence of heavy metal in a sample. The kit comprises a medium and a chromogenic reagent applied to the medium, the chromogenic reagent containing a metal sensitive ligand. The medium is chitosan wherein the chitosan acts as an immobilizeer holding particles of the metal sensitive ligand thus enabling the ligand to react with heavy metal in the sample.